Implementasi Sistem Informasi Pendaftaran Calon Pengantin Berbasis Website - Nurma Yunita Wijaya; Lukman Hakim; Ahmad Taqwa Martadinata (Journal of Information System Research (JOSH), 2023)
Technological developments in the era of globalization are currently experiencing rapid and rapid progress. Currently information technology is developing in accordance with the development of the internet. One of the faster and more rapid developments in information is web-based information technology, which is much needed and can be obtained accurately, quickly and accurately. With a good information system can facilitate the process of applicants or employees in the service process. For offices with a lot of data, processing with technology is very helpful. This online bridal registration system is a web-based system that is useful for assisting prospective brides in registering their marriage. The process of registering a marriage at the KUA in Jayaloka Regency still uses a manual process where the bride and groom come to the KUA to register their marriage and collect information about the terms of marriage. Therefore, the rapid development of information technology encourages the author to register the bride and groom online so that they can help the bride and groom. The design of this study was to create a registration website and data collection was carried out through observation, interviews and literature review. The programming language is PHP and the UI design software uses waterfall. Create a database with MySQL using XAMMP. In testing the implementation of the bride and groom registration system, the author carried out the test using the black box testing system, after carrying out a series of system tests, it was concluded that the system was running well.